Speaking science in a foreign tongue: Plurilingual voices in U.S. universities - Antwi, Wilhelmina (American Journal of STEM Education, 2026)
The internationalization of STEM education has significantly transformed academic discourse in U.S. universities. However, research on how non-native English-speaking STEM students navigate linguistic challenges remains limited. This gap is especially important given that over half of the international students in the U.S. are enrolled in STEM fields, where technical language adds complexity to academic communication. Drawing on Communication Accommodation Theory and translingual perspectives, this study examines how international STEM graduate students navigate language barriers at their host institutions. Through in-depth interviews with 10 international graduate students from Africa and Asia, our analysis reveals systemic challenges, including inadequate institutional support and integration difficulties.